2016
DOI: 10.1590/1519-6984.04615
|View full text |Cite
|
Sign up to set email alerts
|

Vernonanthura polyanthes leaves aqueous extract enhances doxorubicin genotoxicity in somatic cells of Drosophila melanogaster and presents no antifungal activity against Candida spp.

Abstract: Vernonanthura polyanthes (Spreng.) A.J. Vega & Dematt. (Asteraceae), known as "assa-peixe", has been used in ethnomedicine for the treatment of various diseases such as bronchitis, pneumonia, hemoptysis, persistent cough, internal abscesses, gastric and kidney stone pain. Moreover, some studies demonstrated that species of Genus Vernonia present antifungal activity. Due to the biological relevance of this species, the aim of this study was to investigate the toxic, genotoxic, antigenotoxic and antifungal poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…A previous study using Drosophila as a model to evaluate the toxic potential of V. polyanthes leaves aqueous extract showed no toxic, genotoxic, and antigenotoxic activity in the experimental conditions tested using the wing somatic mutation and recombination test SMART/wing (Guerra-Santos et al, 2016). Different from that, at the present work we identified a toxic and cytotoxic activity of V. polyanthes.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…A previous study using Drosophila as a model to evaluate the toxic potential of V. polyanthes leaves aqueous extract showed no toxic, genotoxic, and antigenotoxic activity in the experimental conditions tested using the wing somatic mutation and recombination test SMART/wing (Guerra-Santos et al, 2016). Different from that, at the present work we identified a toxic and cytotoxic activity of V. polyanthes.…”
Section: Discussioncontrasting
confidence: 77%
“…In addition to those phytochemical screenings, previous characterization also have been shown that different V. polyanthes leaves extracts present compounds such as: flavones chrysoeriol-7-O-glycuronyl, acacetin-flavones 7-O-glycuronyl, sesquiterpenes, triterpenes, lactones piptocarphin A and piptocarphin B, glaucolide A, chlorogenic acids, coumarins, glycosides, steroids, saponin glycosides, and alkaloids (Gallon et al, 2018;Martucci et al, 2014;Igual at al., 2013;Souza et al, 2008). Despite this variety of metabolites, some studies pointed that flavonoids and terpenoids are the main compounds present in V. polyanthes extracts (Barbastefano et al, 2007;Bohlmann et al, 1981).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…V. polyanthes is used therapeutically as an infusion to treat infections of the respiratory tract, muscle pain, kidney treatments, wounds, sprains, bruises, dislocations, hemorrhoids and uterus infections [18], [20], [23]. In addition, there are in vitro and in vivo tests that demonstrate its diuretic, antihypertensive, anti-hemorrhagic, sedative, abortive, anthelmintic, antiulcerogenic, antirheumatic, healing, anti-inflammatory, antinociceptive, antibacterial, antifungal, leishmanicidal and anti-tumor actions [18], [21], [23], [24], [25], [26], [27], [28], [29].…”
Section: Introductionmentioning
confidence: 99%